(untitled) (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
According to Indonesian Law in 2019, any marriage under the minimum age of 19 years old is considered Early Marriage. Early Marriage hurts physical and psychological health, especially in cases followed by a high-risk teenage pregnancy. The risk of Stunting increases with children born to a teenage pregnancy. The prevalence of Stunting remains high in Indonesia, reaching 23.3% in 2024 for Malang Regency. Our community service was initiated in response to Early Marriage and Stunting in Jabung, a village in Malang Regency. Our purpose is to prevent Stunting through health education and local food innovation by using a community empowerment approach. This aims to enhance cadres’ knowledge of reproductive health and stunting prevention, develop skills as peer educators, share food innovation recipes based on local products, and increase cadres’ understanding of digital marketing. The participants were 30 cadres. The methods were health education lectures, peer educator practice, and cooking demonstrations. After community service showed an increase in cadres’ knowledge from the average score pre-test (57.8) to post-test (85), an increase in cadres’ skills as educators, an increase in the ability of cadres to make healthy food innovations, and cadres also got new knowledge about digital marketing. After the community service, we hope that cadres can apply the latest knowledge to become better educators and share new recipes based on local food innovations for the wider community, as well as apply marketing strategies to increase the value of the local products, which not only will help to prevent Stunting but also improve family and village economy.